Parental Unemployment During the Great Recession and Childhood Adiposity - Jonathan Briody (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2020)
The incidence of adiposity in the early years of life has outgrown the prevalence rate in older children and adolescents globally; however, the relationships between unemployment and weight are predominantly studied in adults. This study examines the relationship between changing economic conditions during the Irish recession and child weight. Fixed effect logistic regression is used to examine the effects of parental unemployment on weight using the Growing up in Ireland infant cohort from 2008 to 2013. This study is the first to use longitudinal anthropometric measurements to estimate the impact of parental unemployment on children's weight before, during and after a recession. Child growth charts are used to quantify children according to overweight for BMI, weight for age, and weight for height measures. For BMI, the probability of a child being overweight is 6 percentage points higher if either parent has experienced unemployment. For weight for age the probability is of similar magnitude across several alternative growth charts and definitions of adiposity. The analysis is repeated, cross-sectionally, for physical activity and diet to clarify mechanisms of effect. The probability of a child consuming healthy food and physical activity with an implied cost is lower if either parent becomes unemployed. A focus on excess adiposity in the early years is of crucial importance as if current trends are not addressed a generation of children may grow up with a higher level of chronic disease.
Keywords: I12; I18; C33; J10; J13; 330; Health; Panel data; Unemployment; The Great Recession; Children